Epidemics, Gender, and Human Capital in Developing Countries - Fabrizio, Stefania (IMF Working Papers; Working Paper ;, 2021)
Epidemics have disrupted lives for centuries with deleterious human capital and economic repercussions. In this paper, we investigate how epidemics episodes have impacted school dropouts in developing countries, considering 623 epidemics episodes across countries from 1970 to 2019. Our estimates show that, on average, epidemics reduce completion rates by about 2.6 and 2.1 percentage points in primary and lower secondary education respectively, with girls more severely affected than boys. Using detailed micro data for Senegal, we also estimate the potential loss of lifelong earnings and find that the potential labor earnings loss from dropping out of primary and secondary school is almost double for girls than for boys.